Condicionantes socioeconômicos e ambientais dos clubes de convergência da renda na Amazônia Legal 1985 a 2007 - SILVA, Gerson Medeiros da (2013)
This paper analyzes the formation of convergence clubs in Amazonia in the period 1985 to 2007 conditional on socio-economic, institutional and environmental. The innovative nature of this work is to test the first time the importance of deforestation and environmental condition of the formation of convergence clubs in the Amazon. A methodology through the nonparametric estimation of kernel densities, the transition matrix and estimation of stochastic kernels to test the evidence of convergence between the municipalities. The results confirmed the hypothesis of convergence, large intra-sectional dynamics of income and the formation of three convergence clubs among the municipalities of legal Amazonia. Human capital appears as a major constraint and the cattle and livestock area has low significance in determining the rent for municipal. Deforestation and institutional variables were not significant for economic growth municipalities of Amazonia.